О северной границе ареала некоторых пресмыкающихся фауны Украины - Щербак, Н.Н. (Вестник зоологии, 1967)
The author informs of the Natrix tessellata Laur. founding in the envirous of Ruzhin (Zhitomir region, the Ukraine) i. e. 200 km to the north of the previously known localities of such findings. Lacerta viridis Laur. was found in large amount in the southern outskirts of Kiev. It is supposed that at the present time these species tend to migrate north.